Deconvolution of Raman spectra for the quantification of ternary high‐pressure phase equilibria composed of carbon dioxide, water and organic solvent. (25th February 2014) - Schuster, Julian J.; Will, Stefan; Leipertz, Alfred; Braeuer, Andreas
<x xml:space="preserve">Abstract</x> The paper reports on a routine to extract the composition of multi‐component mixtures from their Raman spectra at elevated pressures. The strategy is based on fitting weighted Raman spectra of the pure compounds to the measured Raman spectrum of the mixture, also considering the effects of intermolecular interactions onto the Raman spectra by applying Gaussian and Voigt profile deconvolution of the Raman peaks. Thereby, an improved accuracy compared to previous evaluation strategies could be obtained. The more accurate data of the ternary mixtures of carbon dioxide, water and organic solvents are presented. Copyright © 2014 John Wiley & Sons, Ltd.